All-Trans Retinoic Acid Impairs Platelet Function and Thrombus Formation and Inhibits Protein Kinase CßI/δ Phosphorylation - Luo, Qi; Wei, Guangyu; Wang, Xiamin; Xu, Xiaoqi; Ju, Wen; Li, Zhenyu; Gardiner, Elizabeth E.; Andrews, Robert K.; Zeng, Lingyu; Xu, Kailin; Qiao, Jianlin (Thrombosis and Haemostasis, 2019)
All-trans retinoic acid (ATRA) is widely used for induction of complete remission in patients with acute promyelocytic leukemia (APL). ATRA also regulates protein kinase C (PKC) activity. Therapeutic use of ATRA reportedly interferes with hemostatic function in APL patients, including effects on coagulation or other vascular cells, although effects of ATRA on platelets remain unclear. This study aims to investigate the effect of therapeutic-relevant doses of ATRA on platelet function. Human platelets were preincubated with ATRA (0–20 μM) for 1 hour at 37°C, followed by analysis of aggregation, granule secretion, receptor expression by flow cytometry, platelet spreading, or clot retraction. Additionally, ATRA (10 mg/kg) was injected intraperitoneally into mice and tail bleeding time and arterial thrombus formation were evaluated. ATRA inhibited platelet aggregation and adenosine triphosphate release induced by collagen (5 μg/mL) or thrombin (0.05 U/mL) in a dose-dependent manner without affecting P-selectin expression or surface levels of glycoprotein (GP) Ibα, GPVI, or αIIbβ3. ATRA-treated platelets demonstrated reduced spreading on immobilized fibrinogen or collagen and reduced thrombin-induced clot retraction together with reduced phosphorylation of Syk and PLCγ2. In addition, ATRA-treated mice displayed significantly impaired hemostasis and arterial thrombus formation in vivo. Further, in platelets stimulated with either collagen-related peptide or thrombin, ATRA selectively inhibited phosphorylation of PKCßI (Ser661) and PKCδ (Thr505), but not PKCα or PKCßII phosphorylation (Thr638/641). In conclusion, ATRA inhibits platelet function and thrombus formation, possibly involving direct or indirect inhibition of PKCßI/δ, indicating that ATRA might be beneficial for the treatment of thrombotic or cardiovascular diseases.
Keywords: all-trans retinoic acid; platelet; hemostasis; thrombus formation; protein kinase CßI/δ